Isolation of Infectious Bronchitis Virus in Primary cells of the Chick Embryo Chorioallantoic Membrane: M.H. Mohammed1@; M. Hair-Bejo1; Abdel Ameer Husain Zahid2; Amer Alazawy3; Emad Adwar Abdul Ahad4 and Mauida F. Hasoon1 - Mohammed, M. H. (The Iraqi Journal of Veterinary Medicine, 2013)
The susceptibility of the primary chick embryo chorioallontoic membrane cells to infectious bronchitis virus was evaluated after twenty consecutive passages in chick embryo chorioallontoic membrane cells. Virus replication was monitored by cytopathic observation, indirect immunoperoxidase, and reverse transcription polymerase chain reaction (RT-PCR). At 72 hours post-infection in third passage, the cytopathic effect was characterized by rounding up of cells, monolayer detachment, intracytoplasmic brownish colouration was readily observed by immunoperoxidase from 24hours p.i in third passage, and at all times the extracted viral RNA from IBV-infected monolayers was demonstrated by RT-PCR. Tissue culture ineffective dose50 (TCID50) was used to measure virus titration performed on primary chick embryo chorioallontoic membrane cells and the titre in twenty passage was 108.6 TCID50/ml. The results obtained in this study suggested that the primary chick embryo chorioallontoic membrane cells can be used for adaptation infectious bronchitis virus (IBV) and may be considered a step forward for the use of these cells in the future for IBV vaccine production